Optimizing rice yield, quality and nutrient use efficiency through combined application of nitrogen and potassium - Chen, Guangyi; Duan, Qiang; Wu, Chaoyue; He, Xingmei; Hu, Mingming; Li, Congmei; Ouyang, Yuyuan; Peng, Ligong; Yang, Hong; Zhang, Qiuqiu; Jiang, Qinggui; Lan, Yan; et al. (Frontiers in Plant Science, 2024)
Reasonable nitrogen (N) and potassium (K) application rates can effectively improve fertilizer use efficiency, rice yield and quality. A two-year field experiment was conducted with combined application of three N rates (135, 180, and 225 kg ha-1, denoted as N1-N3) and four K rates (0, 90, 135, and 180 kg ha-1, denoted as K0-K3) using super indica hybrid rice cultivar Yixiangyou (YXY) 2115 to explore the effects of co-application of N and K on rice growth and development. The results indicated that the combined application of N and K had significantly interactive effects on dry matter (DM) accumulation, nutrients absorption, N harvest index (NHI), K harvest index (KHI), spikelets per panicle and most rice quality indexes. The highest total DM accumulation (17998.17-19432.47 kg ha-1) at maturity stage was obtained under N3K2. The effect of co-application of N and K on nutrients absorption and utilization varied between the two years and within each year. The highest total N and K accumulations at maturity stage were observed under N3K1 and N3K2, respectively, while the highest N recovery efficiency (NRE) and K recovery efficiency (KRE) were observed under N1K3. High expression levels of N and K metabolism-related genes in rice grains were observed under N3K2 or N3K3, consistent with N and K uptake. Co-application of N and K increased rice yield significantly and the highest yield (6745.02-7010.27 kg ha-1) was obtained under N2K2. As more N was gradually applied, rice appearance quality improved but milling, cooking and eating quality decreased. Although appropriate application of K could improve rice milling, cooking and eating quality, it reduced appearance quality. The optimal milling, cooking and eating quality were obtained under N1K2, while the best appearance quality was obtained under N3K0. Overall, a combination of 135-210 kg ha-1 N and 115-137 kg ha-1 K application rates was recommended for achieving relatively higher yield and better quality in rice production.